Application of Graph Coloring in Compilation of Work Schedules for Dr. General Hospital Nurses Ferdinand Lumbantobing Sibolga - Rifka Helena W Silitonga; Mulyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Preparation of a schedule is needed to regulate the course of work activities, but errors often occur such as schedules that are not according to the rules and schedules that clash, for that we need other alternatives that can help the process of preparing the schedule. An alternative that can be used is Graph Coloring. Graph coloring is the process of giving color to graph nodes so that no neighboring vertices have the same color, the vertices represent the nurses and the edges represent the relationships between nurses. Then coloring the graph nodes with the Welch-Powell algorithm, where each neighboring (related) vertex is not colored with the same color so that nurses with the same criteria have different groups. So that each working group of nurses formed has nurses with each criterion according to predetermined rules and there are no conflicting schedules.